Impact of Internet Culture on Indonesian Values and Moral Decision Making - Basthian A Laoebela; Gerald Aldytia Bunga; Nanny Mayasari; Unggul Sagena (Catuspata, 2023)
As internet usage has grown, so has the influence of internet culture on Indonesian values and moral decision making. The internet provides a platform for the exchange of ideas and perspectives, and it has the potential to shape and transform social and cultural norms and values. For example, internet culture may promote the spread of liberal and progressive ideas, and it may provide a voice to marginalized and underrepresented groups. Exposure to internet culture can influence Indonesian values and moral decision making in a number of ways. One of the key ways is through the exposure to a wider range of ideas, perspectives, and behaviors, which can challenge and broaden existing cultural norms and values. For example, internet culture may expose individuals to more liberal and progressive ideas, promoting greater tolerance and inclusiveness. This study aims to find out how the impact of the internet for Indonesia, especially values and moral decision making. Based on the literature study conducted in this study, it is known that the internet has both positive and negative impacts on Indonesian values and moral decision-making. To minimize negative impacts, strategies such as content filtering, media and digital literacy programs, promoting responsible online behavior, and enforcing online regulations could be implemented. A proactive and multi-faceted approach that considers the specific context and needs of Indonesian society could help to maximize the internet's positive benefits while minimizing its negative impacts.